Digital leadership Competencies in Achieving the Readiness of Arab Universities for Digital Transformation According to ISTE-A standards for Sustainable Development - Salamah, Maram Jaser Bani; Albadarneh , Atieh Mohd; Awais, Buthiana Elias; Daradkah, Amjad Mahmoud; Hourieh, Ali Hussein; Mahmoud, Ashraf Mahmoud; olimat, Saleh Nasser; ALShurman, Muneera M.; Ali, Shaimaa Ali (Journal of Ecohumanism, 2025)
This article surveys the views of faculty members and leaders on the significance of digital leadership competencies necessary to achieve the readiness of Arab universities for digital transformation according to ISTE-A standards. The research methodology involves using the descriptive approach. The research sample consists of (690) faculty members and (105) academic leaders “faculty deans, faculty deputies, department heads” randomly selected from Arab universities. A questionnaire is used as research instrument to achieve the research objectives. The findings indicate that the faculty members and leaders emphasized the significance of all five domains of digital leadership competencies necessary to achieve the readiness of Arab universities for digital transformation at a very high level. The results also show that the domain of vision planner competencies is ranked first with a mean of (4.75), while the domain of system designer competencies with a mean of (4.73). It is also found that the domain of leader enabler competencies is ranked third with a mean of (4.63), while the domain of connected learner competencies is ranked fourth with a mean of (4.55). However, the domain of competencies of the Equity and Citizenship Advocate is ranked last with a mean of (4.37). Given the said results, the study recommends a set of measures related to the university and the academic leaders themselves to ensure the successful implementation of the digital leadership competencies necessary to achieve the readiness of Arab universities for digital transformation.